Motivational stages, anxiety and depression symptoms during smoking treatment - Wilson Vieira Melo; Margareth da Silva Oliveira; Elisa Arrenti Ferreira (Interação em Psicologia, 2006)
Smoking is a public health problem that has victimized many people along the years (Gigliotti, Carneiro & Ferreira, 2001). Motivation is one of the most difficult aspects smokers have to face when they try to stop smoking (Heather, 1992; Di Clemente & Prochaska, 1985). The objective of this quasi-experimental study was to evaluate change in motivational stages during an eight-week smoking cessation treatment. The sample was comprised of 109 subjects who were evaluated in 4 moments, using the URICA, BAI, BDI, FTND Scales and the Monoximeter. The results indicate that the anxiety and depression scores of those who adhered to the treatment were lower than the ones of those who did not (p=0,023 and p=0,022, respectively). In addition, only the sub-scale of “maintenance” showed a significant increase in score (p<0,001), since the other ones maintained the same mean scores. Such increase is not related to the nicotine dependence level (p=0,244). This level did not have any correlation to joining the treatment (p=0,687). The importance in evaluating motivacional stages, anxiety and depression in smokers are discussed, for they seem to be fundamental in this context.